S1 TOMADO: A crossover randomised controlled trial of oral mandibular advancement devices for obstructive sleep apnoea-hypopnoea. (14th November 2013) - Quinnell, TG; Pittman, MA; Bennett, M; Jordan, J; Clutterbuck-James, AL; East, CL; Davies, MG; Oscroft, N; Cameron, M; Chadwick, R; Smith, IE; Morrell, M; et al.
Abstract : Introduction: Obstructive sleep apnoea-hypopnoea (OSAH) causes excessive daytime sleepiness (EDS), impairs quality of life (Qol), and increases cardiovascular disease and road traffic accident risks. Continuous positive airway pressure therapy is effective but undermined by intolerance and cost effectiveness is borderline in milder cases. Mandibular Advancement Devices (MADs) are another treatment option but evidence is lacking regarding their effectiveness compared to no treatment in milder disease. This study compared clinical and cost effectiveness of a range of MADs and no treatment in these patients. Methods: This 4-period, randomised, controlled, crossover trial was undertaken at a UK sleep centre. Adults with mild to moderate OSAH and EDS (Apnoea-Hypopnoea Index (AHI) 5-<30/hour; Epworth Sleepiness Scale score (ESS) > = 9) underwent 6 weeks of treatment with three non-adjustable MADs: self-moulded (SP1); semi-bespoke (SP2); fully-bespoke (bMAD); and 4 weeks no treatment. Primary outcome was AHI scored by a polysomnographer blinded to treatment and analysed by intention to treat. Secondary outcomes included ESS and QoL. Cost effectiveness was evaluated using validated tools, treatment costs and healthcare usage. Results: Ninety patients were recruited. Sixteen withdrew before trial end. Seven did not complete any treatment and were excluded from analyses. All devices reduced AHI against no treatment, by 26% (95%CI 11%, 38%, p = 0.001) for SP1 to 36% (95%CI 24%, 45%, p < 0.001) for bMAD. ESS was 1.51 (SP1) to 2.37 (bMAD) lower versus no treatment (p < 0.001 for all). Compliance was lower for SP1 which was unpopular at trial exit. All devices were cost-effective compared with no treatment at a willingness to pay (WTP) of £20, 000/quality-adjusted life year (QALY), based on mean costs and QALYs. SP2 was most cost-effective up to a WTP of £39, 800/QALY after which, bMAD superseded it. Serious adverse events occurred in four patients (4%). Conclusions: Mandibular Advancement Devices achieve clinically important improvements in mild to moderate OSAH syndrome and are cost effective. A semi-bespoke non-adjustable MAD would appear to be the appropriate first choice in most patients. Future work should explore whether adjustable MADs give additional clinical and cost benefits in this patient group. Funding: NIHR Health Technology Assessment Programme, UK.